Sertraline for Functional Recovery After Acute Ischemic Stroke: A Prospective Observational Study - Stuckart, Isabella; Siepmann, Timo; Hartmann, Christian; Pallesen, Lars-Peder; Sedghi, Annahita; Barlinn, Jessica; Reichmann, Heinz; Puetz, Volker; Barlinn, Kristian (Frontiers in Neurology, 2021)
Background: A neuroprotective effect has been postulated for selective serotonin-reuptake inhibitors (SSRI). We hypothesized that sertraline, which is characterized by less severe adverse effects and more stable pharmacokinetics than classic SSRI, is associated with improved functional recovery in acute ischemic stroke (AIS) patients with motor deficits. Methods: Prospective observational study of consecutive acute ischemic stroke patients who received sertraline for clinically suspected post-stroke depression (PSD) or at high risk for PSD. Eligibility comprised motor deficit caused by AIS (≥ 2 points on NIHSS motor items) and functional independence pre-stroke (mRS ≤ 1). Decision to initiate treatment with SSRI was at the discretion of the treating stroke physician. Patients not receiving sertraline served as control group. Favorable functional recovery defined as mRS ≤ 2 was prospectively assessed at 3 months. Multivariable logistic regression analysis was used to explore the effects of sertraline on 3-months functional recovery. Secondary outcomes were frequency of any and incident PSD (defined by BDI ≥ 10) at 3 months. Results: During the study period (03/2017-12/2018), 114 AIS patients were assigned to sertraline (n=72, 62.6%) or control group (n=42, 37.4%). At study entry, patients in sertraline group were more severely neurologically affected than patients in the control group (NIHSS: 8 [IQR, 5-11] versus 5 [IQR, 4-7]; p=0.002). Also, motor NIHSS scores were more pronounced in sertraline than in control group (4 [IQR 2-7] vs. 2 [IQR 2-4], p=0.001). After adjusting for age and baseline NIHSS, multivariable regression analysis revealed a significant association between sertraline intake and favorable functional outcome at 3 months (OR 3.10, 95% CI 1.02-9.41; p=0.045). There was no difference between both groups regarding the frequency of any depression at 3 months (26/53 [49.1%] versus 14/28 [50.0%] patients, p=0.643). However, fewer incident depressions were observed in sertraline group patients compared to patients in control group (0/53 [0%] versus 5/28 [17.9%] patients, p = 0.004). Conclusions: Our prospective data points toward a signal of improved functional recovery in patients receiving sertraline de novo after AIS.